The Cuban Hippocrates - Rokselys Vigo Rodríguez (Acta Médica del Centro, 2014)
Tomás José Domingo Rafael  del Rosario Romay and Chacón  is known by all cubans as a doctor who applied for the first time, the smallpox spheres of knowledge, so he became a sage who began the Cuban vaccine in Cuba; however, has not disclosed enough about their condition humanist eminent who served in diverse  scientific movement. In this article will focus on these facets of his exemplary life, which could be considered is the Cuban Hippocrates.